Respuesta :

Answer:

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    7/n-(8/7)=0

Step by step solution :

STEP 1:

           8

Simplify   —

           7

The equation at the end of step

1:

 7    8

 — -  —  = 0

 n    7

STEP 2:

           7

Simplify   —

           n

The equation at the end of step

2:

 7    8

 — -  —  = 0

 n    7

STEP 3:

Calculating the Least Common Multiple :

3.1    Find the Least Common Multiple

     The left denominator is :       n

     The right denominator is :       7

       Number of times each prime factor

       appears in the factorization of:

Prime

Factor   Left

Denominator   Right

Denominator   L.C.M = Max

{Left,Right}

7 0 1 1

Product of all

Prime Factors  1 7 7

                 Number of times each Algebraic Factor

           appears in the factorization of:

   Algebraic    

   Factor      Left

Denominator   Right

Denominator   L.C.M = Max

{Left,Right}

n  1 0 1

     Least Common Multiple:

     7n

Calculating Multipliers :

3.2    Calculate multipliers for the two fractions

   Denote the Least Common Multiple by  L.C.M

   Denote the Left Multiplier by  Left_M

   Denote the Right Multiplier by  Right_M

   Denote the Left Denominator by  L_Deno

   Denote the Right Multiplier by  R_Deno

  Left_M = L.C.M / L_Deno = 7

  Right_M = L.C.M / R_Deno = n

Making Equivalent Fractions :

3.3      Rewrite the two fractions into equivalent fractions

Two fractions are called equivalent if they have the same numeric value.

For example :  1/2   and  2/4  are equivalent,  y/(y+1)2   and  (y2+y)/(y+1)3  are equivalent as well.

To calculate equivalent fraction, multiply the numerator of each fraction, by its respective Multiplier.

  L. Mult. • L. Num.      7 • 7

  ——————————————————  =   —————

        L.C.M              7n  

  R. Mult. • R. Num.      8 • n

  ——————————————————  =   —————

        L.C.M              7n  

Adding fractions that have a common denominator :

3.4       Adding up the two equivalent fractions

Add the two equivalent fractions which now have a common denominator

Combine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

7 • 7 - (8 • n)     49 - 8n

———————————————  =  ———————

      7n              7n  

The equation at the end of step

3

:

 49 - 8n

 ———————  = 0

   7n  

STEP

4

:

When a fraction equals zero :

4.1    When a fraction equals zero ...

Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.

Now, to get rid of the denominator, Tiger multiplies both sides of the equation by the denominator.

Here's how:

 49-8n

 ————— • 7n = 0 • 7n

  7n  

Now, on the left-hand side, the  7n  cancels out the denominator, while, on the right-hand side, zero times anything is still zero.

The equation now takes the shape :

  49-8n  = 0

Solving a Single Variable Equation:

4.2      Solve  :    -8n+49 = 0

Subtract  49  from both sides of the equation :

                     -8n = -49

Multiply both sides of the equation by (-1) :  8n = 49

Divide both sides of the equation by 8:

                    n = 49/8 = 6.125

One solution was found :

n = 49/8 = 6.125

Step-by-step explanation:

hope this helps...

The solution of equation [tex](7^2)^4=n^8[/tex] is n = 7

What is an algebraic expression?

"It is a mathematical statement which consists of variables and constants, and some algebraic operations."

What is an equation?

"It is a mathematical statement which consists of equal symbol between two mathematical statements."

What is exponent?

  • "It refers to the number of times a number is multiplied by itself."
  • "For non-zero real numbers a, b, c,  [tex](a^b)^c=a^{b\times c}[/tex]"

For given question,

We have been given an equation [tex](7^2)^4=n^8[/tex]

Consider an algebraic expression on the left side of the above equation.

[tex](7^2)^4[/tex]

Using the properties of exponents we can write it as,

[tex](7^2)^4\\=7^{(2\times 4)}\\=7^8[/tex]

So, given equation becomes,

[tex]7^8=n^8[/tex]

Since power is same, base of above exponents is equal.

⇒ n = 7

Therefore, the solution of equation [tex](7^2)^4=n^8[/tex] is n = 7

Learn more about the exponents here:

https://brainly.com/question/12158740

#SPJ2